TRAINING TATA KELOLA WAKAF BAGI PENGURUS MASJID DI WILAYAH DKI JAKARTA - Ahmad Fauzi; Santi Susanti; Sri Zulaihati; Umi Widyastuti; Erika Takidah; Petrolis Nusa Perdana (Yayasan Education and Social Center, 2021)
Currently, waqf management is focused on waqf management organizations and mosque-based organizations. The number of mosques in DKI Jakarta which reaches 3087 mosques shows that the potential for socialization and management of mosque-based waqf is very large. Therefore, it is considered important to conduct waqf governance training for mosque administrators in the DKI Jakarta area. With waqf governance training, it is hoped that mosque administrators can improve their competence in managing waqf. Good waqf management can encourage greater potential for waqf receipts. The number of mosques in Jakarta is large and tends to be close to the community, allowing the potential for waqf that can be managed by mosques to be even greater and can also be used directly by people in need around the mosque. Jakarta State University as part of community service activities seeks to contribute to the surrounding community through waqf governance training activities, in collaboration with the Association of Islamic Economists (IAEI) for the DKI Jakarta area